Problematika Pembuktian Dalam Sengketa Medis (Analisis Putusan PN Cikarang NO. 120/Pdt.G.2019/PN Ckr) - Sudarmanto, Sudarmanto; Arsanti, Meilan (Adagium: Jurnal Ilmiah Hukum, 2025)
Medical disputes are one of the most complex legal issues, particularly in the process of proving negligence, which must be carried out by the patient or plaintiff. This article examines the challenges of proving medical disputes in Indonesia, with a case study of the Cikarang District Court Decision No. 120/Pdt.G/2019/PN Ckr. In this case, the plaintiff faced difficulties in proving medical negligence, mainly because the complications experienced were considered medical risks that had been previously explained. This analysis highlights the challenges in distinguishing natural complications from actual medical negligence, as well as ethical issues related to the culture of peer protection among medical professionals that affect the objectivity of expert opinions. Additionally, the lack of adequate standards of proof and the role of independent institutions, such as MKDKI, complicate efforts to prove medical disputes. Therefore, it is necessary to strengthen standards of proof in medical disputes, enhance the role of independent expert witnesses, and ensure transparency in informed consent procedures to improve patient protection and legal justice.